A FUNÇÃO SOCIAL DE UMA CLÍNICA-ESCOLA - Haas, Micheli Patrícia Perius; Kryzozun, Lucas Cavalheiro; Utzig, Lidiane De Azevedo; Gering, Juliane; Zanfra, Ariele Rakoski (Salão do Conhecimento, 2017)
Projeto de extensão realizado pelos alunos do curso de Psicologia da Unijuí